1980
DOI: 10.1007/bf00425839
|View full text |Cite
|
Sign up to set email alerts
|

Mistranslation in cells infected with the bacteriophage MS2: Direct evidence of Lys for Asn substitution

Abstract: The coat protein of the bacteriophage MS2 was found to show an increased level of charge heterogeneity when synthesized in Escherichia coli starved for Asn or Lys. No such increase was found when the host was starved for Arg, His Ile or Pro. This is the pattern predicted by "two-out-of-three" codon misreading in the coat protein gene. In the case of Asn starvation, direct measurements of the relative incorporation of Lys demonstrate that the observed charge heterogeneity is the result of mistranslation. Asn st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…As early as the advent of two-dimensional gel electrophoresis in the 1970s, it was observed that under nutritional or environmental stress, cells often produce proteins that seem to deviate from those programmed by the genetic code (54). Starving E. coli for the amino acid asparagines (Asn) leads to readily detectable levels of proteins that contain non-Asn substitutions such as lysine (Lys, (56)). This result was interpreted as Asn starvation decreasing the amount of charged tRNA Asn (which reads AAC/AAU codons) so that the near-cognate tRNA Lys (which reads AAG/AAA codons) can read the Asn codons to make Asn-to-Lys mutant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As early as the advent of two-dimensional gel electrophoresis in the 1970s, it was observed that under nutritional or environmental stress, cells often produce proteins that seem to deviate from those programmed by the genetic code (54). Starving E. coli for the amino acid asparagines (Asn) leads to readily detectable levels of proteins that contain non-Asn substitutions such as lysine (Lys, (56)). This result was interpreted as Asn starvation decreasing the amount of charged tRNA Asn (which reads AAC/AAU codons) so that the near-cognate tRNA Lys (which reads AAG/AAA codons) can read the Asn codons to make Asn-to-Lys mutant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This should lead to a proportionate reduction in the concentration of the corresponding ternary complex, elongation factor Tu (EF-Tu)-GTP-aminoacyl-tRNA, and hence in its ability to compete with near-cognate ternary complexes for reaction with the ribosome (2). However, in E. coli the accuracy of aminoacyl-tRNA incorporation into proteins seems unaffected (6,7), or only moderately affected (8), by amino acid starvation. RelA mutants of E. coli have lost this ability to preserve translational fidelity during starvation; when these strains are starved for an amino acid, the error rate for translation of codons calling for that amino acid increases dramatically (6,7).…”
mentioning
confidence: 96%
“…After a temperature shift to 40°C, peptidyl-tRNA accumulation begins, and less and less tRNA remains available for continued protein synthesis. There is ample evidence that depletion of a tRNA species leads to increased misreading of its corresponding codon(s) (6,8,9,(18)(19)(20). Misreading could keep protein synthesis going for a while at the expense of increased error rates.…”
Section: Discussionmentioning
confidence: 99%